2000
DOI: 10.1136/bmj.321.7266.923
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of community based speech and language therapy in preschool children

Abstract: Objective To compare routine speech and language therapy in preschool children with delayed speech and language against 12 months of "watchful waiting.'' Design Pragmatic randomised controlled trial. Setting 16 community clinics in Bristol. Participants 159 preschool children with appreciable speech or language difficulties who fulfilled criteria for admission to speech and language therapy. Main outcome measures Four quantitative measures of speech and language, assessed at 6 and 12 months; a binary variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
144
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 19 publications
1
144
0
Order By: Relevance
“…Treatment for receptive auditory comprehension lead to significant improvement for the intervention group compared with the control group; however, results did not differ between groups for several expressive and phonology outcomes. 72 …”
Section: Ages 0 To 2 Yearsmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment for receptive auditory comprehension lead to significant improvement for the intervention group compared with the control group; however, results did not differ between groups for several expressive and phonology outcomes. 72 …”
Section: Ages 0 To 2 Yearsmentioning
confidence: 99%
“…One good 72 and 6 fair-quality [77][78][79][80]84,85 studies evaluated speech and language interventions for children who were 2 to 3 years old. The studies reported improvement on a variety of communication domains including clinician-directed treatment for expressive and receptive language, 80 parent-directed therapy for expressive delay, 77,78 and clinician-directed receptive auditory comprehension.…”
Section: Ages 2 To 3 Yearsmentioning
confidence: 99%
See 3 more Smart Citations